Political Connection And Risk-Taking: The Interaction Role Of Corporate Governance Mechanisms - Wong, Wai Yan (2019)
The purpose of this study is to examine whether political connection affects corporate risk-taking. Anecdotal literature often finds political connection positively impact firm performance, but are many possibilities on how it can happen. One of them is that connected firms have more resources and higher capacity to undertake higher risk-taking which may eventually result in higher performance, compared to non-connected firms. Therefore, this study hopes to investigate whether firms that are politically connected may have a different risk-taking propensity as compared to firms that are not politically connected.